Літературна функція «Молитви Єремії пророка»: творча заготовка чи епіграф до рукописної збірки Тараса Шевченка «Три літа»? - Харчук, Р. (Слово і Час, 2022)
У статті уточнено літературну функцію «Молитви Єремії пророка»
та висвітлено проблему ототожнення й самоототожнення Шевченка
з Єремією. На підставі висновків багатьох дослідників та дискусії між
В. Щуратом й І. Франком 1904 р. авторка визначає, що виписка Шевченка з Біблії — епіграф, а не творча заготовка, як це подано в останньому академічному корпусі доробку поета. Цей факт поглиблює й розуміння
творчих пошуків Шевченка 1843—1845 рр., і розуміння рукописної збірки
«Три літа». Дослідниця переконує, що біблійні моделі допомогли Шевченкові створити оригінальний образ української неволі в Російській імперії й українського майбутнього після подолання імперії. The paper clarifies the literary function of Shevchenko’s “Jeremiah’s prayer”. At the same
time, it raises the question of the poet’s identification and self-identification with Prophet
Jeremiah because these issues can only be addressed in conjunction. Based on the findings
of many researchers on “Jeremiah’s prayer” function and the discussion between Shchurat
and Franko in 1904 about Shevchenko and Jeremiah, the author concludes that “Jeremiah’s
prayer” is an epigraph and not a rough workpiece as it is presented in the last collection
of Shevchenko’s works. This fact is important because it may deepen the understanding of
Shevchenko’s creative pursuits in 1843-1845, the reasons for his self-identification with Jeremiah,
and the interpretation of his collection “Three years” where Moscow captivity is a
metaphorical Babylonian one, the ruins of Chyhyryn remind the lost Jerusalem, and Russia
is shown as a new Babylon. In this context, the researcher points out the image of Jeremiah at
the beginning of the collection “Th ree years”; the use of “Jeremiah’s prayer” as an epigraph to
it; the David’s Psalm 136 (137) about the first Babylonian captivity and the retribution upon
Babylon, which may be considered a pretext for Jeremiah’s understanding of the second Babylonian
captivity of Judea; the destruction of Jerusalem and its restoration; and finally the
motive of atonement taken by Ukrainians for the sins of their fathers in Moscow’s captivity.
Shevchenko developed the last theme following the sample of Jeremiah who saw the cause
of all Judea’s misfortunes in its sins against the Lord. The motive of Ukrainian atonement
for national sins, especially evident in the poems from “Th ree years” having historical connotations,
as in the mystery poem “The Great Cellar”, shows that Shevchenko in 1843-1845
identified himself with Prophet Jeremiah and with King David because these biblical poets
and their artistic models helped him create an original literary image of Ukrainian captivity
in the Russian Empire and the Ukrainian future aft er overcoming the empire.